Gambaran Antara Usia Ibu dan Gravida dengan Kejadian Preeklamsia Berat di Rumah Sakit Umum Daerah Al-Ihsan Provinsi Jawa Barat Tahun 2022 - Alda Olivia Magdalena; Hidayat Widjajanegara; Indri Budiarti (Bandung Conference Series: Medical Science, 2024)
Abstract. Severe preeclampsia is defined as preeclampsia associated with severe complications in the mother and fetus that can cause an emergency situation. The criterion for severe preeclampsia is a blood pressure of 160/110mmHg. Severe preeclampsia is the cause of 30%-40% of maternal deaths in Indonesia. The study aimed to analyze the description of maternal age and gravida status with the occurrence of severe preeclampsia at Al-Ihsan Bandung Regional General Hospital. The study used observational analytic with cross-sectional method. The subjects in this study were pregnant women with severe preeclampsia who were hospitalized at Al-Ihsan Hospital throughout 2022. The sample size amounted to a sample of 270 pregnant women with severe preeclampsia. The sampling technique used purposive sampling that met the inclusion and exclusion criteria by taking medical records in the Obstetrics and Genocology section at Al-Ihsan Regional General Hospital. Data were analyzed by Chi Square Test with a degree of significance of 0.05%. The results of the study from a total of 270 samples analyzed, 150 people (56%) were severe preeclampsia. Maternal age > 35 years with PEB as many as 101 people (77%). Multigravida with PEB amounted to 122 people (81%). Abstrak. Preeklamsia berat didefinisikan sebagai preeklamsia yang berhubungan dengan komplikasi berat pada ibu dan janin yang dapat menimbulkan keadaan yang gawat darurat. Kriteria pada preeklamsia berat adalah tekanan darah 160/110mmHg. Preeklamsia berat adalah penyebab dari 30%-40% kematian maternal di Indonesia. Penelitian bertujuan untuk menganalisis gambaran usia ibu dan status gravida dengan kejadiaan preeklamsia berat di Rumah Sakit Umum Daerah Al-Ihsan Bandung. Penelitian menggunakan analitik observasional dengan metode cross-sectional. Subjek pada penelitian ini adalah ibu hamil dengan preeklamsia berat yang berada di rawat inap RSUD Al-Ihsan sepanjang tahun 2022. Besar sampel berjumlah sampel 270 ibu hamil dengan kejadiaan preeklamsia berat. Teknik pengambilan sampel menggunakan purposive sampling yang memenuhi kriteria inklusi serta ekslusi dengan mengambil catatan rekam medik pada bagian Obstetri dan Genokologi di Rumah Sakit Umum Daerah Al-Ihsan. Data dianalisis oleh Uji Chi Square dengan derajat kemaknaan sebesar 0,05%. Hasil penelitian dari total 270 sampel yang dianalisis, 150 orang (56%) preeklamsia berat. Usia Ibu > 35 tahun dengan PEB sebanyak 101 orang (77%). Multigravida dengan PEB berjumlah 122 orang (81%) .​